Fodor's Peru - McIlvain, Josh. (New York : Fodor's, 2008)
A full-color guide to Peru, featuring practical advice for getting around and recommendations on hotels, restaurants, sights, and shopping, and includes regional highlights and maps.
Includes index.
Young Adult
Keywords: Peru -- Guidebooks; Peru -- Guidebooks